The Figure of Ivan Luchytskyi in the Historiography - Matros, Olha (Pedagogical Discourse, 2013)
The article analyzes the historiography of the studied figure of Ivan Luchytskyi. In particular, the studies of educational, political, scientific and social activities of the scholars, who began to study his legacy during I.Luchytskyi’s life, are characterized. Many researchers have dedicated their works and biographical facts which were placed in the Professors and Lecturers Biographical Dictionary of the Imperial University of St.Vladimir (1834-1884), edited by W.Ikonnikova, as well as in the Brockhaus and Efron Encyclopaedia even during the life of the scientist. Futhermore, the article describes the studies of I.Luchytskhyi’s heritage, made by many scholars of scientific community, since the life of this outstanding person and to this day.